PENERAPAN ISAK 35 PADA LAPORAN KEUANGAN YAYASAN PENDIDIKAN ‘X’ KOTA SURABAYA - Okta Ridawati, Vela; Otik Wiraswati, Mitha; Yuli Yanti Wulansari; Bachtiar Yuliansyah, Rezki (Majalah Ekonomi, 2024)
Non-profit organizations are entities focused on serving societal needs without pursuing profit, instead concentrating on social and environmental issues. Since 1997, these organizations followed the standards outlined in the Statement of Financial Accounting Standards (PSAK) 45. However, in 2019, PSAK 45 was replaced by the Interpretation of Financial Accounting Standards (ISAK) 35. This research aims to assess the implementation and presentation of financial statements by the Education Foundation to determine if it complies with ISAK 35. The study uses a qualitative research method with a comparative approach to examine the current state of the research subject or issue. The findings indicate that the Foundation has not prepared its financial statements according to ISAK 35, which outlines how non-profit organizations should present their financial reports. The Foundation records financial transactions primarily on a cash basis, focusing solely on inflows and outflows. However, ISAK 35, specifically paragraphs 09-12, provides guidance on the necessary adjustments and descriptions for various items in the financial statements of non-profit organizations. As a result, it can be concluded that the X Education Foundation prepares its financial statements in a simplified format, recording only income and expenses. The overall reporting does not conform to the prescribed standards and fails to meet the requirements set by ISAK 35.